New Features in Mucous-Ameloblastoma. A Case Report of rare Entity - Ibrahim Saeed Gataa; Balkees Taha Garib; Noroz Hama Rashid (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2015)
Histologically ameloblastoma showed various forms of metaplastic changes. Evidence of mucous cells is a rare finding and only 9 cases were reported. We present a case of 80 year old male suffered from mandibular swelling for five years duration diagnosed as mucous ameloblastoma. Histopathological examination revealed a lot of mucous pools within the growth, a thin fibrous capsule surrounding the mass and a direct connection between growth islands and oral mucosa. This case highlights the features of rare type of ameloblastoma.